Advantages and Disadvantages of the Cashless Economy - Agnieszka WOJCIK-CZERNIAWSKA (Communications of International Proceedings, 2022)
At the dawn of 2022, the Covid-19 pandemic seems to be behind us and the world economy continues its recovery. The process of disappearance of cash continues its march with different intensities. Many governments and companies are undergoing a process of change, giving more importance to electronic money and digital means of payment. Certain countries hardly use cash anymore, for example the Nordic countries. Fintech companies have burst into prominence and have managed to generate a financial culture that was unimaginable just 20 years ago. Traditional banks and Fintech companies have begun a complex coexistence in this technological era, competing and sharing important advances. Regulations have been established that limit the amount of cash payments, more card transactions are carried out and new payment methods are promoted, from paying with our own cell phone, to paying with virtual and unregulated currencies, as is the case with cryptocurrencies. All of these trends raise different questions about the ultimate demise of cash. On the other hand, the defenders of demonetization allege important reasons in the field of security and the fight against crime. Improvements in digital technology can help limit the “underground economy”, tax evasion and corruption of officials. In this sense, the circulation of cash is seen as an enhancer of illegal activities. Additionally, the profound economic and political interests present in the different countries around the possibilities of issuing cash to finance government management must be considered; the interests of companies in the financial sector to control all the processes associated with the payment and information management network; and, the desire of citizens to have cash for their daily operations or savings. The research method is based on the analytical-descriptive method, whose purpose is both to present: the history of money, the economic and economic conditions regarding currencies, the changes that occur in the field of traditional currencies due to the interference of new technologies, addressing the issue of electronic money and its application in the market European and world as well as showing the future of electronic money and its advantages and disadvantages.
Keywords: effective; without effective; advantages; disadvantages.